Parental Obesity and Early Childhood Development - Yeung, Edwina H. (Pediatrics, 2017)
BACKGROUND: Previous studies identified associations between maternal obesity and childhood neurodevelopment, but few examined paternal obesity despite potentially distinct genetic/epigenetic effects related to developmental programming. METHODS: Upstate KIDS (2008–2010) recruited mothers from New York State (excluding New York City) at ∼4 months postpartum. Parents completed the Ages and Stages Questionnaire (ASQ) when their children were 4, 8, 12, 18, 24, 30, and 36 months of age corrected for gestation. The ASQ is validated to screen for delays in 5 developmental domains (ie, fine motor, gross motor, communication, personal-social functioning, and problem-solving ability). Analyses included 3759 singletons and 1062 nonrelated twins with ≥1 ASQs returned. Adjusted odds ratios (aORs) and 95% confidence intervals were estimated by using generalized linear mixed models accounting for maternal covariates (ie, age, race, education, insurance, marital status, parity, and pregnancy smoking). RESULTS: Compared with normal/underweight mothers (BMI <25), children of obese mothers (26% with BMI ≥30) had increased odds of failing the fine motor domain (aOR 1.67; confidence interval 1.12–2.47). The association remained after additional adjustment for paternal BMI (1.67; 1.11–2.52). Paternal obesity (29%) was associated with increased risk of failing the personal-social domain (1.75; 1.13–2.71), albeit attenuated after adjustment for maternal obesity (aOR 1.71; 1.08–2.70). Children whose parents both had BMI ≥35 were likely to additionally fail the problem-solving domain (2.93; 1.09–7.85). CONCLUSIONS: Findings suggest that maternal and paternal obesity are each associated with specific delays in early childhood development, emphasizing the importance of family information when screening child development.